2021
DOI: 10.7717/peerj.11464
|View full text |Cite
|
Sign up to set email alerts
|

The effects of genotypes and media composition on callogenesis, regeneration and cell suspension culture of chamomile (Matricaria chamomilla L.)

Abstract: Background Chamomile is an important herb being used widely for medicinal purposes. Its multitherapeutic, cosmetic, and nutritional values have been established through years of traditional and scientific use and research. Increased use of medicinal plants necessitates rational use as well as sustainable production of such genetic resources. Plant in vitro micro-propagation poses unique opportunities for sustainable production of medicinal herbs, their regrowth and conservation. The present stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 38 publications
(44 reference statements)
2
7
0
Order By: Relevance
“…Swat-II) callus grew well using MS medium augmented using 2,4-D and BA. [22]., reported similar observations for Sorghum bicolour. L. [23], suggested that MS media augmented through 3.0 mg/l of 2,4-D led to better callus development and higher numbers for most genotypes they researched.…”
Section: Callus Inductionsupporting
confidence: 70%
“…Swat-II) callus grew well using MS medium augmented using 2,4-D and BA. [22]., reported similar observations for Sorghum bicolour. L. [23], suggested that MS media augmented through 3.0 mg/l of 2,4-D led to better callus development and higher numbers for most genotypes they researched.…”
Section: Callus Inductionsupporting
confidence: 70%
“…This step will establish an aseptic culture to be carried out in the following phase of micropropagation. On the other hand, numerous factors affect the explant's development in the growth and multiplication phase [25,26]. For instance, the source of plant material, kind of explant, the type of basal media and its strength and plant growth regulators and its concentration [27].…”
Section: Introductionmentioning
confidence: 99%
“…The surface sterilization protocol increased the aseptic percentage in the shoot-tip explants. However, it also led to necrosis of the explants, thus making it harder to rejuvenate them [ 14 , 15 , 16 ]. Contamination in cultured explants can occur within three to ten days after inoculation, as mentioned by Chen and David [ 17 ].…”
Section: Discussionmentioning
confidence: 99%